Monotonicity among Judges: Evidence from Judicial Panels and Consequences for Judge IV Designs - Sigstad, Henrik (American Economic Review, 2026)
Judge IV designs rely on monotonicity—each judge being weakly stricter than more lenient judges in all cases. I measure monotonicity in judicial panels in five different settings and find that it is violated in up to 50 percent of nonunanimous cases. The monotonicity violations are not detected by conventional tests, but they would typically induce little bias in judge IV estimates. (JEL C26, K41, K42, O17)